Effect of feeding additives on total solids of cows` milk - Sathian C T (Department of Dairy Science, College of Veterinary and Animal Sciences, 1992)
A study was undertaken to evaluate effect of feeding acetic acid (200 ml/day), sodium bicarbonate (1.5% of the concentrate), potassium carbonate (1.2% of concentrate) and magnesium oxide (0.8% of the concentrate) on solids content of cow’s milk.